Delegate satisfaction from conference service quality and its impact on future behavioural intentions - Chryssoula Chatzigeorgiou; Evangelos Christou; Ioanna Simeli (Proceedings of ICCMI 2017, Thessaloniki, Greece, 21-23 June 2017, 2017)
This study presents the development of a conceptual model that demonstrates the dynamic nature of the relationship between service quality and delegate satisfaction in the conference sector, based on theories derived from social psychology and previous research in the marketing, management, and services literature. The model was tested using sample data from delegates of four different academic conferences and was modified as a result of empirical results. The final model improves understanding of the relationship between service quality and delegate satisfaction because these constructs were examined from the process perspective of a conference experience; it portrays service quality and satisfaction in the context of a complete system.
Keywords: L83; Z33; M31; 330; conference marketing; delegate satisfaction; service quality; future behavioural intentions